Pelaksanaan Pengembangan Model Pembelajaran Tahsin Berbasis Audio Visual dengan Menggunakan Aplikasi Mubirasmani di PTKI Provinsi Riau - Nelvawita, Nelvawita (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
Reading the Qur'an is an important factor for every Muslim, because it is of worship value for the reader. Along with the times, a pattern of learning development in reading the Qur'an appears, so that this important lesson always looks interesting and not boring. The objectives of this study are to knowing the implementation of the development of audio-visual-based tahsin learning models at PTKI Riau Province. The type of research used is Research and Development using the ADDIE development pattern (Analysis, Design, Develop, Implement, and Evaluation). The sampling technique used was purposive sampling. The results of the study concluded is development of audio-visual-based Mubirasmani tahsin learning model can be accessed on the https://mubirasmani.com/ page. This application is assessed by adding up the results of the assessment of technology experts and learning materials experts which have reached 89.22% with a very valid category. Thus it can be concluded that the audio-visual tahsin al-Qur'an learning media based on the Mubirasmani android application at the Riau Province Universities is very effective in facilitating the ability to understand and apply tahsin science at the Riau Province Islamic Universities in Pekanbaru City.